(untitled) (Journal of Mechanical Engineering, 2010)
The static pressure distributions on a group of cylinders with either square or rectangular cross-section having rounded corners are presented. The test is conducted at the exit end of an open circuit wind tunnel with uniform velocity of 14.2 m/s across the cylinder with Reynolds number of 2.87 x 104 and 4.20 x 104 based on the side dimension of the cylinder normal to the direction of the approach flow. The experiment is performed for a group consisting of two cylinders one behind the other along the flow direction with different side dimensions at zero angle of attack for various interspacing between the cylinders. It is observed from the experimental results that there is appreciable effect of the side dimension and interspacing on the drag coefficient of the cylinders. The results are applicable to a group consisting of two tall buildings one behind the other along the wind velocity direction and each building of either square or rectangular cross-section having rounded corners. The wind load on the downstream cylinder decreases remarkably due to the presence of the cylinder in the upstream side. Keywords: Wind load; Group of buildings. DOI: 10.3329/jme.v41i1.5361 Journal of Mechanical Engineering, Vol. ME 41, No. 1, June 2010 42-49